2021
DOI: 10.1161/circinterventions.120.009342
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Change in Nutritional Risk on Mortality and Heart Failure After Transcatheter Aortic Valve Replacement

Abstract: Background: Limited data are available regarding change in the nutritional status after transcatheter aortic valve replacement (TAVR). This study evaluated the prognostic impact of the change in the geriatric nutritional risk index following TAVR. Methods: TAVR patients were analyzed in a prospective and observational study. To analyze the change in nutritional status, geriatric nutritional risk index of the patients was calculated on the day of TAVR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Recent studies reported that patients with improved malnutrition after TAVR had better survival rates than patients with remained malnourished [ 32 , 33 ]. Considering it, knowing a low TCBI before the procedure may allow for identifying patients for necessary nutritional intervention and improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported that patients with improved malnutrition after TAVR had better survival rates than patients with remained malnourished [ 32 , 33 ]. Considering it, knowing a low TCBI before the procedure may allow for identifying patients for necessary nutritional intervention and improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 27 , 28 It has been recently reported that those patients who are malnourished undergoing transcatheter aortic valve replacement that improve their nutritional status after the intervention have better prognostic outcomes. 29 This fact may be seen as a signal for a potential target to improve outcomes both in aortic and mitral population, if the nutrition status can be optimized beforehand. Unfortunately, we did not assess nutritional status change after mitral repair, and this hypothesis is speculative.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because of their interactions with the cardiovascular system, hepatorenal function and nutritional status do not remain static, and their postoperative assessment may thus inform the clinical course beyond that of baseline evaluation alone. Egbe et al 11 showed an association between temporal deterioration of hepatorenal function and transplant‐free survival in patients with Ebstein anomaly, while Gonzalez Ferreiro et al 28 found that patients remaining at nutritional risk after transcatheter aortic valve implantation exhibited an increased risk of mortality and HF hospitalization. Extending these findings, our study demonstrates that concomitant hepatorenal dysfunction and malnutrition persisted in a substantial proportion (15%) of patients undergoing valvular surgery.…”
Section: Discussionmentioning
confidence: 99%